Cultural values and digital media usage in social communication. Statistical analysis across EU countries - Chiriac, Horia-Costin; Grecu, Silviu-Petru; Vranceanu, Elena-Simona (Technium Social Sciences Journal, 2025)
In the context of globalization and the rapid pace of digitalization, social media are becoming the main spaces for communication, interaction, and identity formation. Online social networks function as "social networks" — structures of connections between individuals or groups, through which information, norms, values, resources, and social support circulate. This paper aims to link trust in media and online media consumption to the cultural values and socio-economic conditions. Therefore, the study aims to estimate significant differences in the research variables using Hofstede’s cultural model. Using a sample of EU member states, the paper highlights the extent to which trust in online news is determined by cultural factors compared to economic ones. Using quantitative research methods based on T-test and multiple regressions, the paper creates a comprehensive framework for understanding the role played by cultural values and economic conditions in shaping trust in media and online media consumption for news and political information.